Multifunctional poly(d,l-lactide-co-glycolide)/montmorillonite (PLGA/MMT) nanoparticles decorated by Trastuzumab for targeted chemotherapy of breast cancer - Sun, B. (2014)
10.1016/j.biomaterials.2007.09.038